2001
DOI: 10.1038/35106527
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi-liquid nature of the normal state of itinerant-electron ferromagnets

Abstract: A century of research on magnetic phenomena had led to the view that the normal state of itinerant-electron ferromagnets such as Fe, Ni and Co could be described in terms of the standard model of the metallic state or its extension known as the nearly ferromagnetic Fermi liquid theory. In recent years, however, a large body of observations has accumulated from various complex intermetallic systems that raises the possibility that this assumption might be wrong. Here we examine this issue by means of high-preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
421
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(453 citation statements)
references
References 24 publications
30
421
1
Order By: Relevance
“…[13][14][15][16][17] The shortcomings of current theories for itinerant quantum criticality have been re-emphasized recently. 18 A necessary assumption is an underlying well behaved systems of non-interacting fermions. Imada et al 19 have suggested itinerant quantum criticality arises either from proximity to a first-order transition (quantum tricriticality), a metal-insulator transition (not the case here), or a Lifshitz transition, which accompanies a change in topology of the Fermi surface.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…[13][14][15][16][17] The shortcomings of current theories for itinerant quantum criticality have been re-emphasized recently. 18 A necessary assumption is an underlying well behaved systems of non-interacting fermions. Imada et al 19 have suggested itinerant quantum criticality arises either from proximity to a first-order transition (quantum tricriticality), a metal-insulator transition (not the case here), or a Lifshitz transition, which accompanies a change in topology of the Fermi surface.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…In the same way as pressure can initially decrease the freezing point of water, physicist have been able to use pressure to decrease the Curie temperature to absolute zero temperature, leading to a quantum phase transition. Surprisingly, a variety of unconventional properties have been unveiled near the ferromagnetic quantum phase transition [1], including superconductivity [2][3][4][5], non-Fermi liquid behavior [6], tri-criticality [5,[7][8][9][10], and complex magnetic structures [11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…The press used at the ILL is equipped with an electronic load cell that accurately measures the load force of the press and the displacement sensor of the piston, which makes it possible to determine the friction and the pressure at room temperature by increasing and decreasing the load. Figure 4 shows the relation between the applied force or the expected pressure in the cell at room temperature, and the effective pressure applied to the sample below 50 K. The pressure at low temperature is estimated from the critical temperature of MnSi as reported in ref [17], where the long range helimagnetic order sets-in at zero field. The figure shows that the pressure losses due to friction and the freezing of Fluorinert amount to about approximately 20%.…”
Section: Tests and Operation Of The Cellmentioning
confidence: 99%
“…Relation between the applied force or the expected pressure in the cell at room temperature, and the effective pressure applied to the sample below 50 K as deduced from the critical temperature of MnSi. The pressure at low temperatures is estimated from the critical temperature of the helimagnetic order at zero field as reported in [17]. …”
Section: Tests and Operation Of The Cellmentioning
confidence: 99%
See 1 more Smart Citation